2016
DOI: 10.4142/jvs.2016.17.4.479
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of an immunochromatographic assay using a gp51 monoclonal antibody for the detection of antibodies against the bovine leukemia virus

Abstract: Infection of cattle with bovine leukemia virus (BLV) has been observed and reported worldwide, including in Korea. The onsite identification of infected cattle would help decreasing and eradicating BLV infections on farms. Here, we present a new immunochromatographic assay that employs monoclonal antibodies (MAbs) for the detection of antibodies against BLV in the field. BLV envelope glycoprotein (gp)51 was expressed in E. coli, and MAbs against recombinant BLV gp51 were generated for the development of an imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Immunochromatographic tests for serodiagnosis of brucellosis in animal species have been described [22][23][24][25]. Kim et al have developed an immunochromatographic system for the detection of specific antibodies against the bovine leukemia virus [26]. Koo et al, Sotnikov et al, and Bermúdez et al have shown the feasibility of using immunochromatographic assays for the serodiagnosis of tuberculosis [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Immunochromatographic tests for serodiagnosis of brucellosis in animal species have been described [22][23][24][25]. Kim et al have developed an immunochromatographic system for the detection of specific antibodies against the bovine leukemia virus [26]. Koo et al, Sotnikov et al, and Bermúdez et al have shown the feasibility of using immunochromatographic assays for the serodiagnosis of tuberculosis [27][28][29].…”
Section: Introductionmentioning
confidence: 99%